INTEGRATION OF INNOVATIVE TECHNOLOGIES FOR TEACHING ECOLOGY IN HIGHER EDUCATIONAL INSTITUTIONS OF DEVELOPED COUNTRIES INTO THE EDUCATION OF UZBEKISTAN - Rasulova Ra’no Ibraximjanovna (Innovate Conferences, 2025)
This article analyzes innovative technologies used in the process of teaching ecology in higher education institutions of developed countries.nnotation. This article analyzes innovative technologies used in the process of teaching ecology in higher education institutions of developed countries. On the basis of international experiences, the possibilities of identifying effective pedagogical approaches, digital tools and methodologies and applyin.
Keywords: environmental education, innovative technologies, higher education, digital education, international experience, Uzbekistan.